PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 184 PEKANBARU - Sartika, Friska Tri; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research is the low result of learning mathematics in grade V at SDN 184 Pekanbaru with an average value was 64,66. While the KKM mathematical specified school was 75. From 38 students, only 15 students who reached the KKM. The objective of the research is to improve the result of mathematic lesson of V grade students at SDN 184 Pekanbaru with implementation of cooperative learning model type Course Review Horay. This research was classroom action research with two cycles. The subject of this research is student of VA grade with 38 student which consisting of 18 men and 20 women. Based on observational sheet of teacher and students activity showed that teacher and student activity were improved every meeting. The activities of teachers in implementation cooperative learning model type Course Review Horay in the first cycle at first meeting was 75% (enough) and a second meeting was 79% (enough). And second cycle at first meeting was 88% (good) and the second meeting was 92% (very good). Activity of students in the first cycle at first meeting was 71% (enough) and a second meeting was 75% (enough). And second cycle at first meeting was 83% (good) and the second meeting was 92% (very good). Mathematic learning outcomes before implementation cooperative learning model type Course Review Horay with average 64,66, after implementation cooperative learning model type Course Review Horay average UH I increased by 16,23 to 80,89, and average UH II increased by 28,96 to 93,62. Based on the analysis of data of this study it can be concluded that cooperative learning model type Course Review Horay outcomes mathematic class V SDN 184 Pekanbaru.Key Words : Cooperative learning model type course review horay, mathematics learning outcomes